PEMANFAATAN MEDIA PEMBELAJARAN BERBASIS TIK UNTUK MENINGKATKAN EFEKTIVITAS PEMBELAJARAN PAI DI SMP MA’ARIF 1 PAMEKASAN - Irma Raswati; Diana Kamelia Sunaini; Yeni Sofia; Abd.Mukhid; Risky Ramadhan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The use of Information and Communication Technology (ICT) in Islamic Religious Education (PAI) learning is one step towards improving the quality of learning, making it more effective, innovative, engaging, and relevant to current developments. This study aims to determine the use of ICT media in Islamic Religious Education (PAI) learning, the implementation process of ICT-based learning, the level of effectiveness of its use, and the supporting and inhibiting factors, along with potential solutions. The discussion showed that the types of ICT media used in Islamic Religious Education (PAI) learning are Chromebooks, laptops, LCD projectors, instructional videos, PowerPoint presentations, the internet, learning apps, social media, and a digital version of the Quran. Using different types of media can boost students' interest, motivation, participation, and understanding of what they are learning. Using ICT media has been shown to make learning more engaging and fun, allowing students to grasp religious content in a clearer and more relevant way. But, using ICT-based learning still has many challenges, like not enough facilities and infrastructure, teachers and students having low digital skills, not enough time, and different ways that students learn. Factors that help make learning successful include the skills of the teacher, how ready the students are, the access to learning resources, support from the environment, and effective time management. At the same time, some solutions that can be put in place are enhancing teacher skills through training, making the most of the facilities we have, boosting student motivation to learn, and strengthening the partnership between schools and parents. This, the use of ICT media in Islamic Religious Education learning plays a crucial role in realizing a more effective, interactive, creative learning process that is tailored to the needs of students in the digital era.